(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2013)
Thermophilic L-aminoacylase Geobacillus stearotermophilus was immobilized on silochrome C-80 with glutaraldehyde. Immobilization process does not affect the temperature optima of derived preparations, but increase in the thermal stability of the immobilized aminoacylase was observed. Michaelis constants ( Km) were calculated for N-acetyl-L-methionine, N-acetyl-L-valine and N-acetyl-L-alanine. It was shown that as a result of immobilization Km for N-acetyl-L-methionine increased more than 2-fold.